Thermodynamics and kinetics of hydriding and dehydriding reactions in Mg-based hydrogen storage materials - Li, Qian; Lu, Yangfan; Luo, Qun; Yang, Xiaohua; Yang, Yan; Tan, Jun; Dong, Zhihua; Dang, Jie; Li, Jianbo; Chen, Yuan; Jiang, Bin; Sun, Shuhui; et al. (Journal of magnesium and alloys, 2021)
Mg-based materials are one of the most promising hydrogen storage candidates due to their high hydrogen storage capacity, environmental benignity, and high Clarke number characteristics. However, the limited thermodynamics and kinetic properties pose major challenges for their engineering applications. Herein, we review the recent progress in improving their thermodynamics and kinetics, with an emphasis on the models and the influence of various parameters in the calculated models. Subsequently, the impact of alloying, composite, and nano-crystallization on both thermodynamics and dynamics are discussed in detail. In particular, the correlation between various modification strategies and the hydrogen capacity, dehydrogenation enthalpy and temperature, hydriding/dehydriding rates are summarized. In addition, the mechanism of hydrogen storage processes of Mg-based materials is discussed from the aspect of classical kinetic theories and microscope hydrogen transferring behavior. This review concludes with an outlook on the remaining challenge issues and prospects.